Omnichannel Marketing Communication Strategy about Bandung City Fashion - Nabila Azka, Zahrah (Yayasan Pendidikan Belajar Berdikari, 2024)
The rapid development of digital technology has transformed marketing communication practices in the fashion industry, encouraging brands to adopt omnichannel strategies to meet evolving consumer expectations. This study aims to analyze omnichannel marketing communication strategies implemented by fashion brands in the city of Bandung, a prominent creative and fashion hub in Indonesia. Using a qualitative research approach, data were collected through in-depth interviews with fashion brand owners and marketing practitioners, supported by observations of physical stores and digital platforms, as well as analysis of promotional and communication materials. The findings reveal that fashion brands in Bandung actively integrate online and offline communication channels, with social media and online marketplaces serving as primary platforms for brand storytelling and consumer engagement, while physical stores function as experiential spaces that strengthen customer relationships. Message consistency and visual identity across channels emerge as key factors in effective omnichannel communication. However, the study also identifies challenges related to limited resources, data integration, and performance measurement, particularly among small-to-medium enterprises. This research contributes to the omnichannel marketing communication literature by providing empirical insights from a local fashion industry in a creative urban context and offers practical implications for fashion brands seeking to enhance integrated communication strategies.